Methods for the analysis of tourism potential of rural areas - Mikery Gutiérrez, Mildred Joselyn; Pérez-Vázquez, Arturo (Revista Mexicana de Ciencias Agrícolas, 2018)
The integration of tourism to rural productive activities represents a strategy for improving the living conditions of the inhabitants. Studies have raised the potential of rural areas to integrate tourism activities from different perspectives. The objective of this study was to analyse the research methods used to determine the tourism potential of rural areas and discuss the scope and limitations of these methods. International literature on research methods and approaches used to address the ability of rural areas for tourism in its various forms was also analysed. The methods are grouped by dimension (social, economic, environmental) to determine the tourism potential and research paradigms. Diversity was found in methods from different research paradigms and different disciplines with similar objectives. Besides inconsistencies in the goal of sustainability in rural development; where a dimension of reality is studied and a greater importance is attributed to the biogeographical resources without considering the social and economic dimensions. Integrating different dimensions (social,environmental,economic,politicalandinstitutional) that def ine the characteristics of each territory under a complex approach of the system, considering the interaction between its components and the context.
Keywords: multifunctionality of space; rural tourism; study methods; touristic aptitude